Enhancing security on IPv6 neighbor discovery using trust-ND. - Chong , Yung Wey (Universiti Sains Malaysia, 2017)
Neighbor discovery protocol (NDP) is a core IPv6 protocol for local network operations. Unfortunately, NDP was designed without proper security mechanism which leave IPv6 nodes vulnerable to attacks. The rising trend of insider attacks increases the severity of the risk. To address this issue, IETF ratified Secure Neighbor Discovery (SeND).However,SeND implementation is not trivial due to high complexity which result in poor adoption by OS makers.